Zinc induced structural changes in the intrinsically disordered BDNF Met prodomain confer synaptic elimination - Wang, Jing (2020)
Human brain derived neurotrophic factor (BDNF) encodes a protein product consisting of a C-terminal mature domain (mature BDNF) and an N-terminal prodomain, which is an intrinsically disordered protein. A common single nucleotide polymorphism in humans results in a methionine substitution for valine at position 66 of the prodomain, and is associated with memory deficits, depression and anxiety disorders. The BDNF Met66 prodomain, but not the Val66 prodomain, promotes rapid structural remodeling of hippocampal neurons’ growth cones and dendritic spines by interacting directly with the SorCS2 receptor. While it has been reported that the Met66 and Val66 prodomains exhibit only modest differences in structural propensities in the apo state, here we show that Val66 and Met66 prodomains differentially bind zinc (Zn). Zn2+ binds with higher affinity and more broadly impacts residues on the Met66 prodomain compared to the Val66 prodomain as shown by NMR and ITC. Zn2+ binding to the Met66 and Val66 prodomains results in distinct conformational and macroscopic differences observed by NMR, light scattering and cryoEM. To determine if Zn2+ mediated conformational change in the Met66 prodomain is required for biological effect, we mutated His40, a Zn2+ binding site, and observed a loss of Met66 prodomain bioactivity. As the His40 site is distant from the known region of the prodomain involved in receptor binding, we suggest that Met66 prodomain bioactivity involves His40 mediated stabilization of the multimeric structure. Our results point to the necessity of a Zn2+-mediated higher order molecular assembly of the Met66 prodomain to mediate neuronal remodeling.